Modelling and Finite Element Analysis of an Aircraft Wing using Composite Laminates. Issue 1 (September 2021) - Nath, Arijeet; Anand, Raunika; Desai, Jeet; Sultan, M.T.H.; Aravind Raj, S.
Abstract: The use of finite element analysis is increasingly gaining popularity in the design and analysis of aircraft structures. Also, composite materials in the manufacturing and design of aircraft structures are increasing due to their exceptional properties of high stiffness to weight ratio. Applications include Composite structures are made up of laminates with different fibre orientations, which adversely affects the property of the composites formed. For this study, the three main parts of the aircraft wing are considered for designing: the spars, the ribs, and the aircraft's skin. The spars and made up of aluminium alloy, and the ribs are made up of structural steel. Two different wing models are designed. For Model 1, the skin is assigned Titanium alloy as a material, and for Model 2, CFRP (Carbon Fibre Reinforced Polymer) with resin epoxy is used as the skin material. The ribs are made of structural steel and the spars of titanium alloy for both models. This paper aims to compare the materials mentioned above to find the optimum strength to weight ratio. It was found that, for a given uniform load on the bottom of the aircraft's skin, a weight reduction of 2.37 % was observed in favour of Model 2, the deformation was reduced by 51 per cent, and the von-Mises stress was reduced by ≈ 85%. This paper's results can be used in manufacturing structural components of UAV, especially the wings due to lighter weight and more flexibility and durability than standard titanium alloys and the significant role played by the orientation of the plies in deciding the strength of the composite.